Former les (futur·e·s) enseignant·e·s aux aspects relationnels et émotionnels du métier - Sandrine Biémar; Line Fischer
For both teachers and students, school life is full of varied relational experiences. However, few devices exist in initial teacher training to develop relational and emotional skills of future teachers (Espinosa, 2020; Goyette, 2020). The device presented here aims to make up for this lack in training. After describing the context of initial teacher training in French-speaking Belgium, we define relational and emotional skills and specify their importance for the teacher, the student and learning. This is followed by a description of our devices and its pedagogical goals. Analysis of the evaluation data suggests that future teachers perceive the usefulness of the content and the importance of being prepared for these central aspects of the profession. Finally, various avenues are suggested for the development of such training devices, in particular the inclusion of validated scientific theories, concrete experimentation and peer exchanges.